Adapting to Climate Change in Modern Policing The Rise of the "Eco-Cop" - Matczak, Anna.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access brief explores the profoundly accelerating impact of climate change on law enforcement globally. Drawing on the concept of climatisation, it examines how, on one hand, rising temperatures, extreme weather events, resource scarcity, and sustainability transitions pose new challenges for the evolving role of law enforcement in a changing climate.On the other, these developments also present opportunities to adapt and transform the ways the police do policing. This book builds on the author$1 (Bs earlier research into the impact of climate change on police work. It combines interdisciplinary research and 23 expert interviews to, systematize current knowledge in the field. The aim is to provide a comprehensive understanding of how climate change intersects with policing at societal, organizational, and individual levels. This volume is ideal for policymakers, practitioners, and researchers working at the intersection of climate change and policing.s
Chapter 1. Introduction -- Chapter 2. Setting the scene -- Chapter 3. The changing landscape of crimes and harms -- Chapter 4. Feeling the heat -- Chapter 5. Policing civil disobedience -- Chapter 6. Policing disasters -- Chapter 7. Green organisational reset -- Chapter 8. Resilience and adaptive policing -- Chapter 9. Eco-cops -- Chapter 10. Conclusions.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Criminology; Environmental sciences -- Social aspects; Crime -- Sociological aspects; Crime Control and Security; Environmental Social Sciences; Crime and Society